Evaluating the safety and effectiveness of α-blockers versus mirabegron for medical expulsive therapy in ureteral calculi: A Systematic review and meta-analysis. - Huilei Yan; Xiaoni Li; Xiaobo Zheng; Yuanshan Cui; Jing Huang; Yan Cheng (PLoS ONE)
Introduction and aim The main categories of drugs employed for medical expulsive therapy in patients with ureteral calculi (UC) are alpha-blockers (α-B) and beta-adrenoceptor agonists. This meta-analysis evaluated the safety and effectiveness of α-B versus mirabegron (MIR) in treating UC. Methods From January 1980 to October 2024, we extensively searched the Pubmed, Web of science, Cochrane and EMBASE databases to identify randomized controlled trials (RCTs) that compared the effectiveness of α-B and MIR in managing UC. Furthermore, a systematic review and meta-analysis were carried out. Results The meta-analysis included six publications with 592 patients, comparing α-B with MIR. The stone expulsion rate (SER) was found to be significantly greater in the α-B group than in the MIR group, as indicated by an odds ratio (OR) of 1.51 (95% confidence interval [CI]: 1.05 to 2.16, P = 0.03) in the meta-analysis. However, no significant differences were found between the α-B group and the MIR group for stone expulsion time (SET) (mean difference [MD]: 1.20; 95% CI, -2.71 to 5.10; P = 0.55), pain episodes (PE) (MD: 0.36; 95% CI, -0.04 to 0.76; P = 0.07), or analgesic requirements (MD: 0.79; 95% CI, -0.37 to 1.94; P = 0.18). The α-B group exhibited a significantly higher incidence of adverse events compared to the MIR group for orthostatic hypotension (OR 12.16, 95% CI 3.36 to 43.95, P = 0.0001), headache (OR 3.46, 95% CI 1.41 to 8.49, P = 0.007), and retrograde ejaculation (OR 16.30, 95% CI 5.87 to 45.31, P < 0.00001). While in the dizziness (OR 1.65, 95% CI 0.67 to 4.09, p = 0.28), it made no difference. Conclusions Our meta-analysis identified a substantial enhancement in the SER among patients with UC who received α-B therapy instead of those who were administered MIR therapy. Nonetheless, α-B therapy was connected to an increased risk of adverse events. Systematic review registration PROSPERO, ID CRD42024595934.